The practice of pluralism congregational life and religious diversity in Lancaster, Pennsylvania, 1730 - 1820 - Häberlein, Mark 1966- (Pennsylvania State Univ. Press, 2009)
"Studies the development of religious congregations in Lancaster, Pennsylvania, from 1730 to 1820. Focuses on German Reformed, Lutherans, Moravians, Anglicans, and Presbyterians. Also examines how Roman Catholics, Jews, and African Americans were absorbed into this predominantly white Protestant society"--Provided by publisher